-2(p-5)+7p=-6

Simple and best practice solution for -2(p-5)+7p=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(p-5)+7p=-6 equation:


Simplifying
-2(p + -5) + 7p = -6

Reorder the terms:
-2(-5 + p) + 7p = -6
(-5 * -2 + p * -2) + 7p = -6
(10 + -2p) + 7p = -6

Combine like terms: -2p + 7p = 5p
10 + 5p = -6

Solving
10 + 5p = -6

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 5p = -6 + -10

Combine like terms: 10 + -10 = 0
0 + 5p = -6 + -10
5p = -6 + -10

Combine like terms: -6 + -10 = -16
5p = -16

Divide each side by '5'.
p = -3.2

Simplifying
p = -3.2

See similar equations:

| -7f=72-f | | 2n+8=2-6 | | -15x+5x^2=0 | | 8(7x-3)=24x | | (10x+10−x)/(10x−10−x)=5 | | 13(x-2)=8x+4 | | 4x+8=15x-25 | | [3x]+8=9 | | 2z+32=126 | | 4-15u=4u^2 | | z+(z+32)=126 | | 4[2x-3]=28 | | 5(7x-6)=35x+4 | | n/8-12=-1 | | 11x-24=-11 | | 17a+26=-42 | | 5x+25/6= | | .40x+.05(6-x)=.10(-60) | | .125m=125 | | 4y=x^2-4 | | H=78+30t+-16t^2 | | 4a-ab=a | | (5x-7)(2x+1)=10x(x-4) | | -8x^2+46x-30=17 | | 6x-2x+8=+5+8 | | 8x-x^2=24 | | 16(x+3)=7(x-5)-9(x+4)-7 | | 6x^2-48x=36 | | 11a^3-11a= | | -32x=34x-x+1 | | 3x^2*18x+37=0 | | ny+mx=c |

Equations solver categories